The derivative of y in terms of x is denoted by d/(dx)y or y' .
For the given problem: y =1/2[xsqrt(4-x^2)+4arcsin(x/2)] , we apply the basic derivative property:
d/(dx) c*f(x) = c d/(dx) f(x) .
Then,
d/(dx)y =d/(dx) 1/2[xsqrt(4-x^2)+4arcsin(x/2)]
y’ =1/2 d/(dx) [xsqrt(4-x^2)+4arcsin(x/2)]
Apply the basic differentiation property: d/(dx) (u+v) = d/(dx) (u) + d/(dx) (v)
y’ =1/2[d/(dx) (xsqrt(4-x^2))+ d/(dx) (4arcsin(x/2))]
For the derivative of d/(dx) (xsqrt(4-x^2)) , we apply the Product Rule: d/(dx)(u*v) = u’*v =+u*v’ .
d/(dx) (xsqrt(4-x^2))= d/(dx)(x) *sqrt(4-x^2)+ x * d/(dx) (sqrt(4-x^2))
Let u=x then u'= 1
v= sqrt(4-x^2) then v' =-x/ sqrt(4-x^2)
Note: d/(dx) sqrt(4-x^2) = d/(dx)(4-x^2)^(1/2)
Applying the chain rule of derivative:
d/(dx)(4-x^2)^(1/2)= 1/2(4-x^2)^(-1/2)*(-2x)
=-x(4-x^2)^(-1/2)
=-x/(4-x^2)^(1/2) or - –x/sqrt(4-x^2)
Following the Product Rule, we set-up the derivative as:
d/(dx)(x) *sqrt(4-x^2)+ x * d/(dx) (sqrt(4-x^2))
= 1 * sqrt(4-x^2)+ x*(-x/sqrt(4-x^2))
= sqrt(4-x^2)-x^2/sqrt(4-x^2)
Express as one fraction:
sqrt(4-x^2)* sqrt(4-x^2)/ sqrt(4-x^2)-x^2/sqrt(4-x^2)
=( sqrt(4-x^2))^2/ sqrt(4-x^2) –x^2/sqrt(4-x^2)
=( 4-x^2)/ sqrt(4-x^2) –x^2/sqrt(4-x^2)
=( 4-x^2-x^2)/ sqrt(4-x^2)
=( 4-2x^2)/ sqrt(4-x^2)
Then, d/(dx) (xsqrt(4-x^2))= ( 4-2x^2)/ sqrt(4-x^2)
For the derivative of d/(dx) (4arcsin(x/2)) , we apply the basic derivative property: d/(dx) c*f(x) = c d/(dx) f(x) .
d/(dx) (4arcsin(x/2))= 4 d/(dx) (arcsin(x/2))
Apply the basic derivative formula for inverse sine function: d/(dx) (arcsin(u))= (du)/sqrt(1-u^2) .
Let u =x/2 then du=1/2
4d/(dx) (4arcsin(x/2))]= 4*(1/2)/sqrt(1-(x/2)^2)
= 2/sqrt(1-(x^2/4))
=2/sqrt(1*4/4-(x^2/4))
= 2/sqrt((4-x^2)/4)
= 2/ (sqrt(4-x^2)/sqrt(4))
=2/ (sqrt(4-x^2)/2)
=2*2/sqrt(4-x^2)
=4/sqrt(4-x^2)
Combining the results, we get:
y' = 1/2[d/(dx) (xsqrt(4-x^2))+ d/(dx) (4arcsin(x/2))]
=1/2[( 4-2x^2)/ sqrt(4-x^2)+4/sqrt(4-x^2)]
=1/2[( 4-2x^2+4)/ sqrt(4-x^2)]
=1/2[( -2x^2+8)/ sqrt(4-x^2)]
=1/2[( 2(-x^2+4))/ sqrt(4-x^2)]
=(-x^2+4)/ sqrt(4-x^2)]
or y'=(4-x^2)/ sqrt(4-x^2)]
Applying Law of Exponents: x^n/x^m= x^n-m :
y' =(4-x^2)/ sqrt(4-x^2)
=(4-x^2)^1/ (4-x^2)^(1/2)
=(4-x^2)^(1-1/2)
=(4-x^2)^(1/2)
Final answer:
y'=(4-x^2)^(1/2)
or
y'=sqrt(4-x^2)
Thursday, March 28, 2013
y = 1/2 (xsqrt(4-x^2) + 4arcsin(x/2)) Find the derivative of the function
Subscribe to:
Post Comments (Atom)
Why is the fact that the Americans are helping the Russians important?
In the late author Tom Clancy’s first novel, The Hunt for Red October, the assistance rendered to the Russians by the United States is impor...
-
The poem contrasts the nighttime, imaginative world of a child with his daytime, prosaic world. In the first stanza, the child, on going to ...
-
There are a plethora of rules that Jonas and the other citizens must follow. Again, page numbers will vary given the edition of the book tha...
-
The given two points of the exponential function are (2,24) and (3,144). To determine the exponential function y=ab^x plug-in the given x an...
-
Robinson Crusoe, written by Daniel Defoe, is a novel. A novel is a genre defined as a long imaginative work of literature written in prose. ...
-
Hello! This expression is already a sum of two numbers, sin(32) and sin(54). Probably you want or express it as a product, or as an expressi...
-
The title of the book refers to its main character, Mersault. Only a very naive reader could consider that the stranger or the foreigner (an...
-
The only example of simile in "The Lottery"—and a particularly weak one at that—is when Mrs. Hutchinson taps Mrs. Delacroix on the...
No comments:
Post a Comment